2005
DOI: 10.1016/j.apnr.2004.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Changing the tide: an Internet/video exercise and low-fat diet intervention with middle-school students

Abstract: Abstract:The rising tide of obesity erodes the health of youths and many times results in adult obesity. The purpose of this investigation was to examine the effectiveness of an eight-session health promotion/transtheoretical model Internet/video-delivered intervention to increase physical activity and reduce dietary fat among low-income, culturally diverse, seventh-grade students. Those who completed more than half the sessions increased exercise, t(103) = −1.99, p = .05, and decreased the percentage of dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
201
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(210 citation statements)
references
References 31 publications
(27 reference statements)
3
201
0
3
Order By: Relevance
“…Multimedia can be used to present exercise interventions economically, engagingly, effectively, and efficiently (5,6). This is important for pregnant and postpartum women, who have significant exercise barriers such as fatigue, limited time, child care, and lack of exercise knowledge (7).…”
Section: Significance and Purposementioning
confidence: 99%
“…Multimedia can be used to present exercise interventions economically, engagingly, effectively, and efficiently (5,6). This is important for pregnant and postpartum women, who have significant exercise barriers such as fatigue, limited time, child care, and lack of exercise knowledge (7).…”
Section: Significance and Purposementioning
confidence: 99%
“…8 Until now only three computertailored interventions on eating behaviours for adolescents have been evaluated. [9][10][11] In the first study, 9 the effectiveness of a tailored intervention to reduce fat intake was investigated in families with two adolescents. After 4 weeks, there was a reduction in the percentage of energy from fat, but only in those adolescents with high baseline fat intake.…”
Section: Introductionmentioning
confidence: 99%
“…The intervention was effective for reducing the percentage of energy from fat. 10 In the third intervention, 11 all students in the classroom went through a single computer-tailoring intervention on fat intake on individual computers. The intervention showed a decrease in fat intake in two subsamples, namely girls in technical-vocational education and in boys and girls following general education who had read the whole advice provided.…”
Section: Introductionmentioning
confidence: 99%
“…55 Additional studies have found web-based programs to result in increases in physical activity and improved dietary intake in children as young as 8 years of age. [56][57][58][59] There are many web sites with information related to child obesity, some with interactive games to increase children's nutritional and physical activity knowledge and skills. Most are designed to promote health and prevent obesity, rather than as interactive sites to help children who are already overweight, and few sites contain online tracking components.…”
Section: Introductionmentioning
confidence: 99%